How Listeria monocytogenes organizes its surface for virulence - Carvalho, F (2014)
Listeria monocytogenes is a Gram-positive pathogen responsible for the manifestation of human listeriosis, an opportunistic foodborne disease with an associated high mortality rate. The key to the pathogenesis of listeriosis is the capacity of this bacterium to trigger its internalization by non-phagocytic cells and to survive and even replicate within phagocytes. The arsenal of virulence proteins deployed by L. monocytogenes to successfully promote the invasion and infection of host cells has been progressively unveiled over the past decades. A large majority of them is located at the cell envelope, which provides an interface for the establishment of close interactions between these bacterial factors and their host targets. Along the multistep pathways carrying these virulence proteins from the inner side of the cytoplasmic membrane to their cell envelope destination, a multiplicity of auxiliary proteins must act on the immature polypeptides to ensure that they not only maturate into fully functional effectors but also are placed or guided to their correct position in the bacterial surface. As the major scaffold for surface proteins, the cell wall and its metabolism are critical elements in listerial virulence. Conversely, the crucial physical support and protection provided by this structure make it an ideal target for the host immune system. Therefore, mechanisms involving fine modifications of cell envelope components are activated by L. monocytogenes to render it less recognizable by the innate immunity sensors or more resistant to the activity of antimicrobial effectors. This review provides a state-of-the-art compilation of the mechanisms used by L. monocytogenes to organize its surface for virulence, with special focus on those proteins that work "behind the frontline", either supporting virulence effectors or ensuring the survival of the bacterium within its host.